2009
DOI: 10.1097/cmr.0b013e3283252feb
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratin expression in malignant melanoma: potential application of in-situ hybridization analysis of mRNA

Abstract: Occasional reports indicated cytokeratin (CK) protein expression (mainly by immunohistochemistry) in malignant melanoma (MM) and suggested an association with unfavorable clinical parameters. However, the mRNA expression of CK and its clinicopathologic significance in MM has not been specifically evaluated. We investigated the mRNA and protein expression of nine CKs in melanoma cell lines and tissues, in particular the prognostic significance of CK18 mRNA expression. Reverse transcription (RT)-PCR (CK6-10, 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 17 publications
3
12
0
Order By: Relevance
“…Cytokeratin expression in melanoma has been reported previously, 5,10,28 but usually involves simple keratins; the expression of CK20, as was found in this case, is distinctly unusual in melanoma. In a series of melanoma cell lines and tissues analyzed for mRNA and protein expression of a panel of cytokeratins, none was found to express CK20.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Cytokeratin expression in melanoma has been reported previously, 5,10,28 but usually involves simple keratins; the expression of CK20, as was found in this case, is distinctly unusual in melanoma. In a series of melanoma cell lines and tissues analyzed for mRNA and protein expression of a panel of cytokeratins, none was found to express CK20.…”
Section: Discussionsupporting
confidence: 73%
“…In a series of melanoma cell lines and tissues analyzed for mRNA and protein expression of a panel of cytokeratins, none was found to express CK20. 10 Wen et al recently reported a 27-year-old woman with a primary, non-pigmented right scalp melanoma containing intimately admixed glandular elements. 33 The melanoma component of that tumor stained for classic melanocyte markers (S100, HMB-45, MiTF-1, and PNL2), whereas the carcinomatous component was positive for cytokeratins AE1/AE3 and Cam5.2, as well as MiTF-1, suggesting true transdifferentiation of melanoma into carcinoma, however, no genetic analysis was performed to prove a clonal relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Welldescribed examples of this phenomenon include keratin expression in angiosarcoma, 2 leiomyosarcoma, 3 and Ewing sarcoma, 4 and synaptophysin expression in alveolar rhabdomyosarcoma. 5 It is less widely appreciated that melanomas too may show aberrant expression of various immunohistochemical markers, with a relatively small number of reports, of melanomas showing expression of intermediate filaments other than vimentin (e.g., keratins, desmin, neurofilament protein, and glial fibrillary acidic protein) [6][7][8] and/or neuroendocrine markers. [9][10][11] Over the past several years, we have seen in consultation a significant number of melanomas in which aberrant expression of intermediate filaments and/or neuroendocrine markers obscured the correct diagnosis, and prompted consideration of various non-melanocytic neoplasms, including carcinoma, rhabdomyosarcoma, neural neoplasms, and various neuroendocrine tumors.…”
mentioning
confidence: 99%
“…Spiking experiments showed a !60% recovery rate of 4, 20, 100 and 500 spiked SkMel28 cells when assessed by qPCR amplification of cytokeratin 8 (KRT8) and 18 (KRT18) RNA. The SkMel28 cell line strongly expresses these intermediate filament proteins and KRT18 expression has been previously identified as an adverse prognostic factor in melanoma [8].…”
Section: Melanoma Ctc Enrichment Techniquesmentioning
confidence: 99%